Innovative Behavior of Indonesian Pharmaceutical Employees: The Role of Psychological Empowerment and Leadership - Kusumaputri, Erika Setyanti; Gustia, Sekar Putri Wahyuning (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Innovative behavior is considered a critical and essential factor for companies in theworld of work. This study aims to determine the extent to which psychological empowermentinfluences the innovative behavior of employees working in pharmaceutical companies, withtransformational leadership and transactional leadership as moderators. The research subjectswere 115 employees from various pharmaceutical companies across ten cities in Indonesia.Innovative behavioral scales, psychological empowerment scales, transformational leadershipscales, and transactional leadership scales were used to collect the data. Subgroup analysis andmoderated regression analysis were used to analyze the data. The results show thattransformational leadership has a higher score compared to transactional leadership. This resultindicates that the hypothesis is accepted. Namely, that psychological empowerment is relatedto innovative behavior. Specifically, the correlation between variables showed thattransformational leadership has a more substantial effect than transactional leadershipKeywords: innovative behavior; psychological empowerment; transactional leadership; transformational leadership.